2020
DOI: 10.1097/prs.0000000000006549
|View full text |Cite
|
Sign up to set email alerts
|

Carpal Tunnel Release without a Tourniquet: A Systematic Review and Meta-Analysis

Abstract: Background: Open carpal tunnel release is commonly performed with the use of a tourniquet. The combination of local anesthetic and epinephrine with a pneumatic tourniquet helps provide clear visualization during decompression of the median nerve. There has been a rapid expansion of literature challenging the use of tourniquets in open carpal tunnel release. Consequently, the local anesthesia/no tourniquet approach has become increasingly popular. The authors evaluated the outcomes of awake open car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
0
13
1
1
Order By: Relevance
“…In contrast to our expectations and the results of others, the painful experience of the tourniquet did not affect the overall pain experienced perioperatively nor the patient satisfaction (Olaiya et al, 2020). One possible explanation might be that the pain experienced by the tourniquet did not add to the injection pain already experienced.…”
contrasting
confidence: 99%
“…In contrast to our expectations and the results of others, the painful experience of the tourniquet did not affect the overall pain experienced perioperatively nor the patient satisfaction (Olaiya et al, 2020). One possible explanation might be that the pain experienced by the tourniquet did not add to the injection pain already experienced.…”
contrasting
confidence: 99%
“…Many surgeons use a tourniquet when performing surgical procedures for carpal tunnel syndrome to induce hemostatic effects and to obtain a clear operative field. Recently, Olaiya et al [19] evaluated the outcomes of wide-awake open carpal tunnel release with and without a tourniquet. According to their systemic review and meta-analysis, the use of a tourniquet induces significantly more pain with no significant clinical benefit when compared with the wide-awake technique in which no tourniquet is used in carpal tunnel decompression.…”
Section: Parametermentioning
confidence: 99%
“… 6 Zero intra- or postoperative complications reported in our study substantiates the robust safety profile of the standard OCTR. Our wide-awake (local anesthesia) and no tourniquet policy for OCTR received strong support from a recent meta-analysis published by Olaiya et al 33 The paper reported that “tourniquet use causes significantly more pain with no added clinical benefit as compared with using a wide awake, no tourniquet approach in CTR.”…”
Section: Discussionmentioning
confidence: 88%